The mompreneurs and its contribution on family prosperity: Insight from women empowerment of Payungi community - Nugroho, Dwi (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2023)
This study intends to observe and investigate the increased activity of Muslim women (housewives) as entrepreneurs, the influence of women entrepreneurs on the family economy, and community (NGo) contributions to empowering women, mentorship, education, and expanding capacities. In a qualitative study employing a phenomenological approach, information was gathered by observing and interviewing six members of the empowerment community (two of whom were the initial initiators) and five women (housewives). Meanwhile, documentation studies are optimized in order to deepen the data analysis outcomes. Data from primary sources were evaluated and validated using triangulation techniques. The results reveal that, first and foremost, entrepreneurship is a new economic activity for Muslim women (housewives). Second, women entrepreneurs working together in a culinary tourism destination have a favorable impact on the family's economic well-being. Third, the community's presence (NGo) in developing women entrepreneurs' knowledge, capacities, and competencies in the notion of empowerment is the foundation for the transformation of women into entrepreneurs. The Payungi community serves as a role model for empowerment by optimizing the existence of a religious space, the Entrepreneurial Pesantren, as a space for women's education. The empowerment process pushes women to continuously develop their capabilities, such as optimizing social media, smartphone applications, and product branding content. This study requires additional research in order to acquire more comprehensive results by taking into account the opinions of academia, the media, and the greater business. This research becomes a proposal for government institutions and non-governmental organizations, which is empowering or want to empower.